Characteristics Between New Oil and Used Oil by Using Laser Light Intensity and Lux Meter - Putri, Mala Desrinda Dwi; Slamet, Rifai; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Tests on the characteristics of making new oil and used oil by using laser light intensity and lux meters have been done. The purpose of this study is to distinguish the characteristics of the light intensity between fresh oil and used oil. In this study used an alternative method to the light intensity Lux meter. To get the data is done by varying the distance from the laser to the sample as much as five times. Based on data obtained from testing the intensity of light on new oil and used oil can be concluded that the valu e of the light intensity at the new oil is greater than the used oil. New oil has a light intensity of I = (0.122591964) Cd and used oil has a light intensity of I = (0.017841741) Cd.